STUDY OF VALUE CO-CREATION WITH THE DART MODEL IN THE DEVELOPMENT OF MSME - Setiawan, Bagus (Nusantara Economics and Entrepreneurships Journals, 2024)
One effective digital marketing strategy today is through co-creation marketing. Co-creation places consumers as parties who actively share to create value or products. This study aims to determine the form of value co-creation in the Keripik Tempe Rohani MSME business with the DART model (Dialogue, Access, Risk Assessment, Transparency) as a strategy in product innovation and development while evaluating value co-creation at Keripik Tempe Rohani with the DART model. The results showed that Keripik Tempe Rohani builds an image towards customers by prioritizing customer service and satisfaction. Keripik Tempe Rohani makes good use of social media, one of which is in the context of openness to customers and potential customers. Keripik Tempe Rohani has been good at applying the DART concept in order to create image and value. Although some things can be maximized again, each model makes a positive contribution and is believed to be able to contribute to strengthening the business.